2014
DOI: 10.3390/nu6010207
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Overweight in Children: An Update

Abstract: The clinical presentation of celiac disease in children is very variable and differs with age. The prevalence of atypical presentations of celiac disease has increased over the past 2 decades. Several studies in adults and children with celiac disease indicate that obesity/overweight at disease onset is not unusual. In addition, there is a trend towards the development of overweight/obesity in celiac patients who strictly comply with a gluten-free diet. However, the pathogenesis and clinical implications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 69 publications
(121 reference statements)
3
75
1
15
Order By: Relevance
“…Celiac patients are at risk of overweight/obesity especially during the first year after initiating GFD; probably influenced by the fact that they can eat without suffering symptoms and feeling ill and that their absorptive capacity improves. If this is combined with consuming high-calorie gluten-free foods, the patient will gain more weight than desired [83]. Mariani et al [84] reported that fat and protein intake in celiac adolescents was higher than recommended and that commercially available gluten-free biscuits were richer in saturated fat than their gluten-containing equivalents [84].…”
Section: And Nutritional Statusmentioning
confidence: 98%
“…Celiac patients are at risk of overweight/obesity especially during the first year after initiating GFD; probably influenced by the fact that they can eat without suffering symptoms and feeling ill and that their absorptive capacity improves. If this is combined with consuming high-calorie gluten-free foods, the patient will gain more weight than desired [83]. Mariani et al [84] reported that fat and protein intake in celiac adolescents was higher than recommended and that commercially available gluten-free biscuits were richer in saturated fat than their gluten-containing equivalents [84].…”
Section: And Nutritional Statusmentioning
confidence: 98%
“…Besides the social restrictions and economic burden, 6,11,49 it is possible that the often nutritionally unbalanced diet predisposes some patients to suboptimal intake of vitamins and trace elements and to obesity. 50,51 Further, despite the promising short-term results, there is a risk that dietary adherence declines later in adolescence and adulthood, when follow-up usually becomes less frequent and responsibility for daily treatment shifts from the parents to the patients themselves. This issue has been scantily studied, but a few years ago Van Koppen and colleagues reported good adherence and improved health in a majority of screen-detected children even 10 years after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of children's anthropometric data evolution with CD has been studied and in some cases, children with normal weight at the time of diagnosis evolve to a state of pre-obesity or obesity during follow-up of GFD [11,12,33,34,35,36]. Despite the relevance of this subject, there is insufficient monitoring and scarce published data for the anthropometric evolution of CD Portuguese children, reinforcing the adequacy and necessity of the present study.…”
Section: Introductionmentioning
confidence: 83%
“…It is generally accepted that GFD provides the decrease of systemic symptoms and patient's weight recover [18,49,50,51]. However, the nutritional adequacy of this diet has been questioned, mainly because there is conflict data regarding anthropometric parameters for children with CD [11,32,33,34,35,36].…”
Section: Discussionmentioning
confidence: 99%